2019
DOI: 10.3389/fonc.2019.00730
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Chinese Herbal Medicine on Ovarian Cancer After Reduction Surgery and Adjuvant Chemotherapy: A Systematic Review and Meta-Analysis

Abstract: Background: Ovarian cancer (OvC) is a malignant tumor which invades ovarian epithelium and interstitium. Reduction surgery combined with adjuvant chemotherapy is standard treatment for OvC patients, but the adverse effects due to chemotherapy still remains a major problem. While Chinese herbal medicine (CHM) therapy has a unique therapeutic effect to reduce side effects of chemotherapy by boosting immune system, the evidence of CHM in the treatment of OvC patients are limited. Objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 23 publications
(5 reference statements)
0
22
0
Order By: Relevance
“…Several studies have recognized that TCM have a unique advantage in the treatment of malignant tumors by inhibiting the growth of cancer cells, enhancing immunity of human body, decreasing cancer relapses and metastases, and mitigating the progress of the disease. [ 17 – 21 , 32 – 38 ] Piao et al [ 21 ] found that complementary treatment with mistletoe extracts can beneficially reduce the side effects of chemotherapy and thus improve QoL of patients with breast, ovarian and nonsmall cell lung cancer. Research by Chan et al [ 18 ] indicated that TCM did not improve QoL of cancer patients but did have some effects in terms of maintaining immune function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have recognized that TCM have a unique advantage in the treatment of malignant tumors by inhibiting the growth of cancer cells, enhancing immunity of human body, decreasing cancer relapses and metastases, and mitigating the progress of the disease. [ 17 – 21 , 32 – 38 ] Piao et al [ 21 ] found that complementary treatment with mistletoe extracts can beneficially reduce the side effects of chemotherapy and thus improve QoL of patients with breast, ovarian and nonsmall cell lung cancer. Research by Chan et al [ 18 ] indicated that TCM did not improve QoL of cancer patients but did have some effects in terms of maintaining immune function.…”
Section: Discussionmentioning
confidence: 99%
“…Research by Chan et al [ 18 ] indicated that TCM did not improve QoL of cancer patients but did have some effects in terms of maintaining immune function. The results of study by Wang et al [ 32 ] showed that the clinical application of Chinese herbal medicine not only significantly enhanced the curative effects of conventional treatment but also effectively improved QoL and clinical symptoms in patients with OC. Tao et al [ 33 ] found that the compound fuling granule (CFG, a traditional Chinese drug) can significantly suppresses OC cell proliferation by cell cycle arrest, apoptosis, and senescence.…”
Section: Discussionmentioning
confidence: 99%
“…TCM plays a crucial role in the pharmaceutical industry, alternative medicine, and many other fields [48][49][50]. However, due to the complex chemical composition and unclear pharmacological mechanism of action of TCMs, it faces great obstacles in pharmacological research, quality control and supervision, modernization, and internationalization [51].…”
Section: Discussionmentioning
confidence: 99%
“…Reduction surgery combined with adjuvant chemotherapy is the standard treatment for OvC patients, but the adverse effects due to chemotherapy still remain a major problem. While CHM therapy has a unique therapeutic effect to reduce side effects of chemotherapy by boosting the immune system, the evidence of CHM in the treatment of OvC patients is limited [13].…”
Section: Efficacy and Safety Of Chm For Ovarian Cancermentioning
confidence: 99%